ОСНОВНЫЕ ПРИЧИНЫ, ОБУСЛАВЛИВАЮЩИЕ ПОЯВЛЕНИЕ НАРУШЕНИЙ И ДИСБАЛАНСА В ЛЕСНОМ ХОЗЯЙСТВЕ И ЛЕСОПОЛЬЗОВАНИИ - Baimbetov, N.S. (Journal of actual problems of jurisprudence, 2019)
In given article the author reveals the principal causes causing occurrence of infringements and a disbalance in a forestry and forest usage.